ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI FOREIGN DIRECT INVESTMENT DI SINGAPURA - Putri Alfiyahnur (2023)
Investment is the first stage for economic development, so investment is an important factor and cog for development, especially foreign investment. Another source of funding from foreign parties that helps the economic development of a country is FDI. Investment is very important to spur development in countries because it can help increase employment, increase income, advance technology, socio-economic development. A country's FDI is influenced by a number of factors. The purpose of this finding is to understand and analyze the long-term and short-term impact on GDP, interest rates and exchange rates for FDI in Singapore in the 1985-2020 period. The population in this finding is Singapore. The sample used for this finding is the period 1985-2020. It can be concluded that there were 35 observers. The type of data used for this finding is secondary data, taken from the World Bank. The research method used is ECM with the help of Eviews 10 software. The independent variables in this finding are GDP, interest rates and exchange rates and the dependent variable is Singapore FDI for the 1985-2020 period. Based on estimation findings and statistical tests, FDI in Singapore from 1985 to 2020 was significantly and negatively affected by interest rate variables in the short term, but positively and significantly affected by GDP in the long term.